Mechanisms of radiation damage and development of structural materials for operating and advanced nuclear reactors - Voyevodin, V.N.; Tolstolutskaya, G.D.; Tikhonovsky, M.A.; Kuprin, A.S.; Kalchenko, A.S. (Вопросы атомной науки и техники, 2021)
Safety of nuclear reactor (NR) and economic of nuclear power are determined to high degree by structural materials. Study of reasons of change of physical-mechanical properties of materials and of their dimensional stability under irradiation; determination of operation life of elements of nuclear power energetic assemblies in different conditions, selection and development of prospective materials with high radiation resistance are the main objectives of radiation material science. In the presented paper, mechanisms of radiation damage of structural materials for nuclear power and problems of development of radiation-resistant materials for operating and advanced NR of new generation are examined. Безпека ядерних енергетичних установок (ЯЕУ) і економічність атомної енергетики багато в чому визначаються конструкційними матеріалами, з яких виготовлені елементи ЯЕУ. Вивчення причин зміни фізико-механічних властивостей матеріалів і їх розмірної стабільності при опроміненні, визначення ресурсу роботи елементів ЯЕУ в різних умовах, вибір і розробка перспективних матеріалів з високою радіаційною стійкістю є основними завданнями радіаційного матеріалознавства. У представленій статті розглядаються механізми радіаційного пошкодження конструкційних матеріалів ядерної енергетики, проблеми та перспективи створення радіаційно стійких матеріалів для діючих реакторів і реакторів нового покоління. Безопасность ядерных энергетических установок (ЯЭУ) и экономичность атомной энергетики во многом определяются конструкционными материалами, из которых изготовлены элементы ЯЭУ. Изучение причин изменения физико-механических свойств материалов и их размерной стабильности при облучении, определение ресурса работы элементов ЯЭУ в различных условиях, выбор и разработка перспективных материалов с высокой радиационной стойкостью являются основными задачами радиационного материаловедения. В статье рассматриваются механизмы радиационного повреждения конструкционных материалов ядерной энергетики, проблемы и перспективы создания радиационно стойких материалов для действующих реакторов и реакторов нового поколения.